Hubungan Antara Efikasi Diri terhadap Hasil Belajar Siswa Kelas V di MIS Amaliyah Cibinong - Ahmad Syarif; Ery Subaeri Ahmad,; Kurnia Fauziah (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
This research was motivated by the problem of self-confidence (self-efficacy). This study aims to determine the relationship between three types of self-efficacy on the learning outcomes of fifth grade students at MIS Amaliyah Cibinong. This research uses a quantitative approach with correlation analysis method. This research was conducted with a population of 327 and the sample was taken by means of random sampling and the sample taken was VA class as many as 26 students. Data collection techniques used are in the form of questionnaires and multiple choice tests. The hypothesis test of this research is the analysis of the product moment correlation coefficient. The results of this study indicate that there is a significant positive relationship between self-efficacy and student learning outcomes in science subjects for class VA MIS Amaliyah Cibinong with an rxy/rcount of 0.765 which is in the strong category. Then it is done > from rtable 0.404 with a large correlation of 58.5%, so that H0 rejected and Hais accepted. This shows that “On the relationship between self-efficacy and learning outcomes for science subjects for class VA MIS Amaliyah Cibinong for the 2021/2022 academic year. Keywords: Self-Efficacy, Learning Outcomes